Measurement properties of the Portuguese version of the Kings’s Brief Interstitial Lung Disease (KBILD) in interstitial lung disease - Marinho, Raquel Vilar (2024)
Introduction and objectives: People with interstitial lung diseases (ILD) present a decline in functional status and health-related quality of life (HRQoL). There are several instruments to assess these patient-centered outcomes, however, their measurement properties for specific populations are often unknown. The aim of this study was to assess the reliability and validity of the King’s Brief Interstitial Lung Disease (KBILD) for Portuguese adults with ILD. Methods: An observational study was conducted with people with ILD recruited from routine pulmonology appointments. Sociodemographic and clinical data [lung function and 6-minute walk test (6MWT)] were retrieved from participants’ medical notes and/or gathered with a structured specific questionnaire. At baseline, the KBILD, the St. George’s Respiratory Questionnaire for idiopathic pulmonary fibrosis (SGRQ-I) and the London Chest Activities of Daily Living (LCADL) were first collected face-to-face, in an interview form. The KBILD was repeated 48h-72h after, via phone call, by two raters (2nd moment and 2nd rater). Reliability measures included Cronbach’s to test internal consistency, intraclass correlation coefficient (ICC2,1) and respective 95% confidence intervals (95%CI) for test-retest and interrater reliability, Bland & Altman 95% limits of agreement (95%LoA) to test the agreement, standard error of measurement (SEM) and minimal detectable change (MDC95) for test-retest measurement error. Validity was assessed with the Spearman correlation coefficient (rho): criterion validity between SGRQ-I and KBILD and construct/divergent validity between lung function, 6MWT and KBILD and between LCADL and KBILD. Floor and ceiling effects were explored by quantifying the number of participants who scored at the maximum (ceiling) or at the minimum (floor) of each questionnaire. If more than 15% were at the maximum or minimum, the questionnaire was considered to have ceiling or floor effect, respectively. Results: 167 people with ILD (63.6 ± 13.8 years old; 48.5% male; FVCpp 86.5 ± 19.7; DLCOpp 61.7 ± 21.0) participated. KBILD showed good to excellent internal consistency (= 0.74 for chest symptoms, = 0.87 for breathlessness and activities, = 0.89 for psychological and = 0.92 for total score), good to excellent test-retest (ICC2,1 = 0.79, 95%CI [0.70;0.85] for chest symptoms, ICC2,1 = 0.83, 95%CI [0.76;0.88] for breathlessness and activities, ICC2,1 = 0.78, 95%CI [0.67;0.86] for psychological and ICC2,1 = 0.83, 95%CI [0.73;0.89] for total score) and inter-rater (ICC2,1 = 0.95, 95%CI [0.92;0.97] for chest symptoms, ICC2,1 = 0.89, 95%CI [0.83;0.93] for breathlessness and activities, ICC2,1 = 0.89, 95%CI [0.82;0.93] for psychological, and ICC2,1 = 0.93, 95%CI [0.88;0.95] for total score) reliability, and good agreement between moments (mean = -3.97, 95%LoA [- 24.16;16.21]) and raters (mean = -0.27, 95%LoA [-14.42;13.88]) for total score, without evidence of systematic bias. The SEM and MDC95 were: 0.40 and 1.10 for chest symptoms, 0.57 and 1.59 for breathlessness and activities, 0.46 and 1.29 for psychological, and 1.16 and 3.22 points for total score. Correlations between KBILD and: i) SGRQ-I were significant, negative, and moderate to high (= -0.54 to -0.86; p < 0.01); ii) LCADL were significant, negative, and moderate to high (= -0.47 to -0.71; p < 0.01); iii) lung function and 6MWT were significant, positive, and small to moderate (= 0.23; p < 0.05 to 0.49; p < 0.01). No floor nor ceiling effects were found. Conclusions: KBILD has good reliability and validity indicators to assess HRQoL in Portuguese adults with ILD.